Workplace Fairness, Information Sharing and Employee Performance in a Budget Setting: An Empirical Study - Suria Zainuddin; Che Ruhana Isa (Gadjah Mada International Journal of Business, 2019)
The importance that workplace fairness and information sharing has on employees’ performance has gained a significant attention from researchers and practitioners. However, no empirical evidence on the combined role of both workplace fairness and information sharing on employee performance has been found so far. Thus, the purpose of this study is to examine the effects of workplace fairness and information sharing on employees’ performance in a budget setting. A set of direct and indirect hypotheses are tested using survey data collected from 108 sub-unit managers from various industries, randomly selected from Bursa Malaysia (the stock exchange of Malaysia). The findings indicate that both workplace fairness and information sharing are positively associated with improved employee performance in a participative budget setting. Furthermore, information sharing mediates the relationship between workplace fairness and employee performance. This suggests that when employees perceive the budgeting process as being fair, they would be more willing to share information, which will then lead to improved employee performance.